Firn density and ice content at sites along the west Expéditions Glaciologiques Internationales au Groenland (EGIG) line, Greenland, 2022 - Joel Harper; Neil Humphrey (Arctic Data Center, 2022)
The thermal and structural transformation that Greenland's firn layer is presently undergoing has important implications for the ice sheet's capacity to retain future melt. This project is directly observing firn evolution with a network of instruments installed within the firn layer and with ice cores sampling the firn. This archive contains data collected at sites located along the lower elevation portion of the Expéditions Glaciologiques Internationales au Groenland (EGIG) line, western Greenland Ice Sheet. The data include the physical stratigraphy measured in firn cores extending to depths of up to ~30 m with measurements of firn density and refrozen ice content. The data were collected as part of an Arctic Observing Network (AON) project funded by the U.S. National Science Foundation. Each of the study sites is located in the Greenland Ice Sheet’s Percolation Zone, the outer flanks of the accumulation zone that experiences surface melt during the summer period. Data collection for this AON project began in 2022, and is expected to continue through 2025. This dataset will be associated with additional datasets, including physical stratigraphy and density measured in ice cores and firn temperature time series measured in core holes, as they become available in future years. Additional sites with will be added in future years, and additional data from existing sites will be collected.